Identifikasi Senyawa Aktif Kulit Batang Ampupu (Eucalyptus alba Reinw. Ex. Blume) dalam Menghambat Pertumbuhan Jamur Fusariummoniliforme - Bernadina Metboki (Fakultas Pertanian, Universitas Timor, 2018)
The fungal-related diseases were responsible as one of many reasons for low production of maize in Ind`onesia. Controlling fungal contaminants using chemical is hazardous for human nowadays. Thus the need of environmental friendly vegetative-based fungicide such as from the extract of Ampupu tree bark is important. The objective of this study was to investigate the antifungal effect from Ampupu tree bark crude extract in response to growth of Fusarium sp, which responsible as the causal agent of corncob rot. The inhibition test on growth of Fusarium sp. by Ampupu tree bark crude extract was performed with diffusion well method on PDA as media. The process involved the infusion of crude extracts at 1.5%, 3.0% and 4.5% concentration, respectively, into diffusion well on each petri disk. Gas Chromatography Mass Spectrometry (GC-MS) was used to identify any active compound contained. The result showed that by in vivo treatment, crude extract of Ampupu tree bark with concentration of 1.5%, 3,0% and 4.5%, were able to inhibit the fungal growth of Fusarium miniliforme as the causal agent of corncob rot with diameter of inhibition zone 0.18 mm, 1.85 mm and 2.01 mm, respectively. The higher the concentration of the crude extract given, the larger the diameter of inhibition zone formed. There were 11 active compound found within Ampupu tree bark methanol-based extract, which could potentially become antifungal, i.e. Ethylbenzene, o-Xylene, ALPHA.-PINENE,DELTA.3-Carene, Azulene(CAS)Cyclopentacycloheptene, Tetradecane(CAS)n-Tetradecane, 2,6-Diisopropylnaphthalene, 7,9-Di-tert-butyl-1-oxaspiro(4,5)deca-6,9-dien, Hexadecanamide, 9-Octadecenamide, (Z)-(CAS)OLEOAMIDE, 1,2-Benzenedicarboxylicacid,mono(2-ethylhexyl).